Hardware-in-the-loop simulation for testing of electro-hydraulic fuel control unit in a jet engine application. (February 2013) - Montazeri-Gh, M; Nasiri, M
A hardware-in-the-loop (HIL) simulation framework for testing an experimental electro-hydraulic fuel control unit (FCU) within the numerical simulation of a turbojet engine is presented. The HIL simulator is used to create control signals, and hydraulic and mechanical loads to emulate the operating conditions with a state-of-the-art hydraulic test bench. In a real engine, the FCU contains a miniature gear-type liquid-fuel pump which is driven at a fraction of the engine rotor speed mechanically by a gear. In this study, the engine is simulated numerically and an electric motor is employed to drive the pump instead of the mechanical system. The real-time simulation of the turbojet engine thermodynamic model is implemented on an industrial personal computer with an input/output board in connection with the electro-hydraulic system. Comparison between the HIL simulation and software simulation of the whole system shows the propriety of the HIL simulation platform to test and evaluate a fuel control system.